ORGANISASI MASSA FRONT MAHASISWA NASIONAL WILAYAH JAMBI 2003-2015 - Deade Misgiupriyadin, Arora Nandia Febrianti (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2017)
AbstracIn the research, the writing aims to explain the movement of youth / students and the dynamics of mass organizations of the national student front of Jambi region 2003-2015. The research method used is historical method which includes heuristic stages, source critic, interpretation and historiography. In this study using the theory of social movements, which can take a collective approach to social movements. Especially the youth / student movement, such as the National Student Front. The results of this study indicate that, FMN organization itself was founded by the student actors in jambi, who have different organizational background as well. Like, students from the organization (PMII, HMI and MPRJ). In the development of FMN organization plays a role in various aspects, so as to increase the role of youth / students and other sectors of society. It can be seen from the development of FMN in Jambi starting from the establishment of FMN in 2003 until 2015. Like, the number of FMN cadres who have now become alumni, who took the role to plunge the community and government. Such as, working in government organizations, NGOs / NGOs, women's organizations, farmers' organizations and others.Keywords : Social, Youth / Student Movement, Organization, Front (unity)